Effectiveness Of Business Capital In Terms Of Business Opportunity Analysis In Klambir Lima Kebun Village, Hamparan Perak District, Deli Serdang Regency - Nina Fadilah; Tri Wulandari (Universitas 17 Agustus 1945 Semarang, 2023)
Business actors have a purpose in analyzing the business that is run some of the objectives are to condition the effectiveness of the use of capital so that the capital used is not used with things that are not yet important in running a business, for example in buying equipment that should not need to be purchased because the old equipment is still feasible and can be used. One of the businesses that can be done business analysis is a business that produces cakes, one of which is donuts. Potato Donuts are a variety of products that are in demand both from old people, teenagers and children. Revenue = Rp. 2.500,00 x 500 = Rp. 1.250.000,00, Profit = Rp. 232,500.00 Business Profit Analysis that can be done is as follows: With income of Rp. 1,250,000.00, a profit of 232,500 per day can be obtained if multiplied for the amount of demand for a fixed product, then a month's income of 12 x Rp. 232,500.00 = Rp. 2,790,00.00 or usually rounded up to Rp. 2. 790. 000,00. With the analysis of business opportunities, it can also be known whether the capital used so far has been effective, it can be seen from the amount of profit obtained always increases in each time period.